2013
DOI: 10.1080/14786435.2012.716908
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability of Σ3 grain boundaries in face centered cubic metals

Abstract: AE3 grain boundaries form as a result of either growth twinning or deformation twinning in face centered cubic (fcc) metals and play a crucial role in determining the mechanical and electrical properties and microstructural stability. We studied the structure and stability of AE3 grain boundaries (GBs) in fcc metals by using topological analysis and atomistic simulations. Atomistic simulations were performed for Cu and Al with empirical interatomic potentials to reveal the influence of stacking fault energy on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…Among low-S GBs, we call particular attention to S3 CTBs because they are often thought to improve mechanical strength and resistance to stress corrosion cracking in metal alloys 16 . These qualities stem from the especially low energy of S3 CTBs, I n t e r g r a n u l a r T r a n s g r a n u la r which is due to perfect, atom-to-atom registry between adjoining crystals at such boundaries 17 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among low-S GBs, we call particular attention to S3 CTBs because they are often thought to improve mechanical strength and resistance to stress corrosion cracking in metal alloys 16 . These qualities stem from the especially low energy of S3 CTBs, I n t e r g r a n u l a r T r a n s g r a n u la r which is due to perfect, atom-to-atom registry between adjoining crystals at such boundaries 17 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The twinned structure can change the energy and the mobility of a mobile interface. It is suggested that the slowest growing grains could lead to the largest fraction of TBs, in that the new twin orientations presumably provide the excess boundary energy required to continue growth [46,75]. Fewer twins generally nucleate at a higher GB migration rate, whereas more twins are found at lower growth rate in pure (NC) metals, since the twinning process is of minor importance as an energy reduction mechanism when reduction in GB area, i.e., fast GG, is strongly operative [50].…”
Section: Twinning-mediated Grain Growthmentioning
confidence: 99%
“…For example, Olmsted et al [83] investigated the GG in Ni through simulations of boundary mobility and misorientation type and showed that the lowest energy boundary is the coherent TB Σ3 601 (111), spanning from 0.06 J m À 2 (coherent TBs) to 1.0 J m À 2 . Although the coherent TB is a Σ3 boundary, it is worth noting only 41 types of Σ3 boundaries were studied in a previous work, all of which have the same misorientation between grains but different inclination planes, therefore exhibiting different mobilities [75,[84][85][86]. GB energy can provide a great driving force for grain coarsening and contribute to which grains coarsen at a faster rate than their neighbors.…”
Section: Detwinning-mediated Grain Growthmentioning
confidence: 99%
“…Experimental studies have uncovered that NT metals have ultrahigh strength/hardness, 24,25,38,[48][49][50] good ductility 25,51,52 and great strain hardening. 25,51,53 Corresponding to these experimental outcomes, a large quantity of theoretical studies are available, such as the intrinsic size effects and plastic anisotropy, the stability of NT structures, 54,55 the effect of surface stress 56,57 and NT structures in CG system on the mechanical properties of metals. [58][59][60][61] Moreover, the electrical conductivity of NT bulk metals is similar to the conventional CG counterpart but much higher than NC metals.…”
Section: Introductionmentioning
confidence: 99%